Role of angiogenesis in melanoma progression: Update on key angiogenic mechanisms and other associated components. (December 2019) - Cho, Woo Cheal; Jour, George; Aung, Phyu P.
Abstract: Angiogenesis, the formation of new blood vessels from existing blood vessels, is a complex and highly regulated process that plays a role in a wide variety of physiological and pathological processes. In malignancy, angiogenesis is essential for neoplastic cells to acquire the nutrients and oxygen critical for their continued proliferation. Angiogenesis requires a sequence of well-coordinated events mediated by a number of tightly regulated interactions between pro-angiogenic factors and their corresponding receptors expressed on various vascular components (e.g., endothelial cells and pericytes) and stromal components forming the extracellular matrix. In this review, we discuss the functional roles of key growth factors and cytokines known to promote angiogenesis in cutaneous melanoma and key factors implicated in the extracellular matrix remodeling that acts synergistically with angiogenesis to promote tumor progression in melanoma, incorporating some of the most up-to-date basic science knowledge from recently published in vivo and in vitro experimental studies.